a.
[tex]2 \sqrt{3} + 9 \sqrt{ 3} - 8 \sqrt{3} = 3 \sqrt{3 } \\ [/tex]
b.
[tex]5 \sqrt{2} - 10 \sqrt{2} + \sqrt{2} + 8 \sqrt{2} = 4 \sqrt{2} [/tex]
c.
[tex] \sqrt{7} + \sqrt{13} + 2 \sqrt{7} - 3 \sqrt{7} + 3 \sqrt{13} - 4 \sqrt{13} = 0[/tex]
d
[tex]4 \sqrt{2} + 30 \sqrt{2} - 7 \sqrt{2} - 5 \sqrt{2} = 22 \sqrt{7} [/tex]
e.
[tex]14 \sqrt{3} - 10 \sqrt{7} + 24 \sqrt{3} - 30 \sqrt{3} + 12 \sqrt{3 } = 20 \sqrt{3} + 10 \sqrt{7} [/tex]
f.
[tex]6 \sqrt{2} + 8 \sqrt{2} - 12 \sqrt{2} + 24 \sqrt{2} = 26 \sqrt{2} [/tex]
g.
[tex]6 \sqrt{3} - 3 \sqrt{3} + 4 \sqrt{3} - 5 \sqrt{3} + 10 \sqrt{3 } = 12 \sqrt{3} [/tex]
h
[tex]10 \sqrt{5} + 5 \sqrt{5} - 8 \sqrt{5} + 3 \sqrt{2} - 9 \sqrt{5} = 3 \sqrt{2} - 2 \sqrt{3} [/tex]
i.
[tex]6 \sqrt{2} - 9 \sqrt{2} +11 \sqrt{2} - 10 \sqrt{2} + 7 \sqrt{2} = 5 \sqrt{2} [/tex]